Exosomal miR-21-5p from glioma associated mesenchymal stem cells promotes the progression and glycolysis of glioblastoma via PDHA1 - Yanbin Zhang; Peng Lv; Qing Zhang; Wei Xiang; Xiaobing Jiang; Zijun Guo; Tao Zhang (Scientific Reports)
Abstract Glioblastoma (GBM) is highly malignant and grows rapidly, and there is currently a lack of effective treatments. Metabolism provides the basis for the occurrence and development of GBM. Pyruvate dehydrogenase A1 (PDHA1) is a key component in both the tricarboxylic acid cycle and glycolysis, playing an important role in the metabolic processes related to cancer, but its role in GBM remains unclear. Glioma associated mesenchymal stem cells (GaMSC) play a significant role in the development of glioma. This study aims to explore the relationship between GaMSC derived exosomes (GAMSC-EXO) and PDHA1, as well as the effects and mechanisms on GBM glucose metabolism. In this study, human GaMSC-derived exosomes were isolated and identified. The role of GAMSC-EXO in GBM proliferation, migration, invasion and glucose metabolism was investigated. The upstream miRNA of PDHA1 was predicted and the relationship between miR-21-5p and PDHA1 in GAMSC-EXO and its effect on GBM glucose metabolism was investigated. We found that GAMSCs promote GBM cell proliferation, migration, invasion and glycolysis by releasing exosomes. After inhibiting GBM glycolysis, GBM proliferation, migration and invasion abilities were weakened. MiR-21-5p in exosomes was identified as the miRNA that affects the above biological behaviors. Mechanismly, miR-21-5p directly binds to the mRNA of PDHA1 and downregulates its transcription, thereby promoting GBM glycolysis. Together, this study demonstrated that exosomal miR-21-5p from GAMSC promoted GBM proliferation, migration, invasion, and glycolysis by targeting PDHA1, which provided novel insights into the metabolic interactions between GAMSCs and GBM cells, emphasizing the importance of exosome-mediated communication in tumor progression.